Analysis of the Impact of HR Development Policies, Work Culture, and Organizational Performance on Competitive Advantage in the Manufacturing Industry in Indonesia - Loso Judijanto; Juni Iswanto (Westscience Press, 2024)
This study investigates the impact of HR development policies, work culture, and organizational performance on competitive advantage within the manufacturing industry in Indonesia. A quantitative research approach was employed, utilizing a sample of 125 manufacturing firms. Data were collected through structured questionnaires administered to HR managers and employees. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) regression was used for data analysis. The findings reveal significant positive relationships between HR development policies, work culture, organizational performance, and competitive advantage. Mediation analysis indicates that organizational performance partially mediates the effects of HR development policies and work culture on competitive advantage. The measurement model demonstrates satisfactory reliability and validity, and the estimated model fits the data well. Hypothesis testing confirms the significant positive effects of HR development policies, organizational performance, and work culture on competitive advantage. Overall, the study underscores the critical role of HR management practices, organizational culture, and performance enhancement strategies in driving competitive advantage in the Indonesian manufacturing industry.